ANALISIS WEB ANALYTICSMETRICS UNTUK MENGOPTIMALKAN REQUEST FREE TRIAL WEBSITE NETMONK.ID - Pratama, Andhika Yoga; Rafiah, Kurnia Khafidhatur (LPPM Universitas dr. Soebandi, 2023)
This research is conducted to analyze the effect ofuser, bounce rate, exit rate, average session duration, and average session per user, which are some variables from web analytics from the Netmonk website, which is an all-in-one monitoring tool service provider in Indonesia that uses a free trial strategy to bring in potential paid users. This study uses secondary data from the Google Analytics tool, which is time series data for 90 weeks,with quantitative methods with the application of SPSS 25. The analysis shows that the user countand average session per user have a significant positive effect on the number of free trial requests on the website